(untitled) (Journal of the College of Basic Education, 2022)
The study aims to treat waste water (sewage) biologically using the method of life filters (trickling filters)) or soil columns, which is one of the methods that have been worked on for years.Whereas, due to the high cost of suitable wastewater treatments, attention began to be paid to the least expensive and well-efficient methods of treatment. A mini experimental system was used to obtain the values ​​of the experimentally studied variables in the treatment of raw wastewater connected to the Rustamiya project for wastewater treatment south of Baghdad. Passing it through columns of sand and gravel layers with different depths, where the variables (TDS, TSS, PO4, NO3, COD, BOD) were studied, and the results indicated high removal efficiency (BOD by 91.4%), (COD by 89.5%) and (TSS by 87.7 %) and medium removal